Ketone transfer hydrogenation reactions catalyzed by catalysts based on a phosphinite ligand. Issue 3 (10th June 2022) - Karakaş, Duygu Elma; Rafikova, Khadichakhan; Baysal, Akin; Meriç, Nermin; Zazybin, Alexey; Kayan, Cezmi; Işik, Uğur; Saparbaykyzy, Islam Sholpan; Durap, Feyyaz; Aydemir, Murat
Abstract: Reaction of (±)-1-(2-furyl) ethanol with an equivalent Ph2 PCl in the presence of Et3 N proceeds in dry toluene under an argon atmosphere to give 1-(furan-2-yl)ethyl diphenylphosphinite (1 ) in good yield. Mononuclear complexes [dichloro(η 6 - p -cymene)(1-furan-2-ylethyl diphenylphosphinite)ruthenium(II)] (2 ), [dichloro(η 6 -benzene)(1-furan-2-ylethyl diphenylphosphinite)ruthenium(II)] (3 ), [chloro(η 4 -1, 5-cyclooctadiene)(1-furan-2-ylethyl diphenylphosphinite)rhodium(I)] (4 ) and [dichloro(η 5 -pentamethylcyclopentadienyl)(1-furan-2-ylethyl diphenylphosphinite)iridium(III)] (5 ) were synthesized and characterized by microanalysis, infrared, MS, and NMR spectroscopies. The complexes are employed as catalysts in transfer hydrogenation of aromatic ketones. The complexes catalyzed reduction of a variety of aromatic ketone substrates bearing electron-withdrawing or donating substituents with very high conversion rates (up to 99%); 5 was the most efficient catalyst for the transfer hydrogenation of ketones. Graphical Abstract: UF0001